2014
DOI: 10.7243/2050-1323-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for end-of-life tire recycling in new tire production, Egypt

Abstract: End-of-life tires constitute one of the biggest environmental concerns in terms of environmental pollution and resources conservation. This study aims to determine the best proportion of reclaimed rubber and crumb rubber to be added as part of the constituents used in the manufacturing of three different tire parts (tread, side wall, and inner liner) in order to produce standard products from a mix of both recycled and original ingredients. Batches were prepared into which reclaimed rubber and crumb rubber wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Due to its low cost, excellent performance and strong interfacial interaction with polymer matrix, RR is widely used in polymer modification, 8–12 especially in tire parts, including tread, 13,14 sidewall, and inner liner 15 . Tire sidewall as the most easily deformed part is prone to aging with deteriorated dynamic mechanical properties and flexing fatigue resistance after long‐term stress and exposure to the environment, which will jeopardize driving safety and comfort 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its low cost, excellent performance and strong interfacial interaction with polymer matrix, RR is widely used in polymer modification, 8–12 especially in tire parts, including tread, 13,14 sidewall, and inner liner 15 . Tire sidewall as the most easily deformed part is prone to aging with deteriorated dynamic mechanical properties and flexing fatigue resistance after long‐term stress and exposure to the environment, which will jeopardize driving safety and comfort 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 18 also reported the improvements in flexing fatigue resistance by adding 8 phr of RR. While Feriha et al 14 claimed that the best proportion of RR as part of the constituents used in the manufacturing of tire sidewall without affecting mechanical properties too much should be 25 phr. Therefore, based on not affecting other basic properties, improving the performance of RR in tire sidewall with proper adding amount is the priority of current research.…”
Section: Introductionmentioning
confidence: 99%